Great Mining Camps of Canada 5. Britannia Mines, British Columbia - Smitheringale, W.G. (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2011)
SUMMARY Britannia was discovered in 1888, began production in 1905, and after nearly 70 years of underground operation produced more copper than any other mine in British Columbia. At one time it was the largest copper mine in the British Empire. Britannia survived the Great Depression, labour shortages brought on by two world wars, and several natural disasters. For most of its life Britannia was owned by the Howe Sound Company of New York, which was formed in 1903 for the purpose of financing the development of the mine. In 1963 it was purchased by Anaconda Canada Limited, which operated the mine until closure in 1974. The Britannia camp encompassed eight separate ore zones located approximately 5 km inland from Britannia Beach. The deposits occurred within a large shear zone in a roof pendant of Mesozoic sedimentary and volcanic rocks enclosed by the Coast Plutonic Complex. Until a few years before mining ceased, the deposits were believed to have been emplaced in structurally favourable sites by hydrothermal fluids; the most recent interpretation of the deposits invokes a VMS model. During the mine’s lifetime, thousands of people worked at Britannia, and they and their families lived in one of two company towns that, until 1956, were accessible only by coastal steamer. After closure, the community of Britannia Beach faced the prospect of becoming a mining ghost town, and the distinction of being the site of an environmental hazard created by acid mine drainage. A solution to the pollution problem was found, and road access to Vancouver combined with the success of the Britannia Mine Museum, a highlight of which is the surviving and spectacular mine concentrator that has been designated a National Historic Site, have given Britannia Beach a promising future. Britannia is historically important from a mining technology viewpoint because it was the first mine in BC to successfully employ froth flotation. It was economically significant because it was an important element in BC’s emerging economy and it is culturally significant because the Britannia communities represented a way of life that was typical of many Canadian mining towns in the first half of the 20th century. Moreover, Britannia Beach has survived and has become a well established community. Additionally, the recent history of Britannia Beach illustrates the importance of environmental considerations related to mine closure.